1992
DOI: 10.1103/physrevlett.69.1904
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the dominant role of resonant enhancement in short-pulse multiphoton ionization

Abstract: We report experimental results which imply that observed peaks in the short-pulse photoelectron spectrum of atoms in high fields result only from a resonant enhancement of the multiphoton ionization rate at the peak of the laser pulse, rather than a two-step process of real population transfer and subsequent single-photon ionization. These results consist of the first identification, in a high intensity (> 10'^ W/cm^) short-pulse photoelectron spectrum, of low-lying states of argon with an ac Stark shift signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 13 publications
3
44
1
Order By: Relevance
“…Usually, ionization is considered as either a "multiphoton" or "tunnelling" process depending on the value of the so-called Keldysh parameter ponderomotive effects, channel-opening and closing etc. were studied, and good agreement between theory and experiment has been achieved [2][3][4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, ionization is considered as either a "multiphoton" or "tunnelling" process depending on the value of the so-called Keldysh parameter ponderomotive effects, channel-opening and closing etc. were studied, and good agreement between theory and experiment has been achieved [2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…In early studies two scenarios resulting in the intensity-independent ATI peak positions were suggested. First one [4] assumes that ionization from an excited state occurs before the intensity has considerably changed, so that it always proceeds at the intensity required to fulfil the resonance condition and accordingly, at some certain value of the ponderomotive shift. If the peak intensity is higher than the resonant value, the resonance condition can be fulfilled somewhere in the laser focus.…”
mentioning
confidence: 99%
“…The two pictures have been used to successfully model experimental results for atoms. [10][11][12][13][14][15] Previous studies provide evidence that strong-field ionization of molecules shares many of the characteristics with those of atoms, 1,2 and indeed the two mechanisms have been observed by previous experimental results for molecules. [1][2][3] N2 is one of the two major ingredients of the atmosphere, and its MPI dynamics in intense femtosecond laser fields has been studies extensively.…”
Section: Introductionmentioning
confidence: 77%
“…2,11 In N2 there are three different low-lying ionization energies (corresponding to the removal of the 3σ g , 1π u , and 2σ u electrons) leading the ionic states X Given 410 nm photons (3.02 eV), a minimum of six-, six-, and seven-photons are necessary for ionization to X (15.58 eV), A (16.70 eV), and B (18.75 eV) ionic final states at zero fields, respectively. When the laser intensity is raised, the electrons acquire significant ponderomotive energy.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation